In Situ Measurement of Lithium-Ion Cell Internal Temperatures during Extreme Fast Charging. Issue 14 (1st January 2019) - Huang, Shan; Wu, Xianyang; Cavalheiro, Gabriel M.; Du, Xiaoniu; Liu, Bangzhi; Du, Zhijia; Zhang, Guangsheng
Abstract : Here we report an investigation of Li-ion cell thermal behaviors during extreme fast charging by in situ measurement of its internal temperatures. An experimental 2 Ah LiNi0.6 Co0.2 Mn0.2 O2 /graphite pouch cell with embedded micro-thermocouples was developed and charged as fast as 7C at room temperature. With forced convection air cooling, the cell core temperature increased by 22.5°C in 5 minutes during 7C charging while it increased by less than 1.5°C during 1C charging. The difference between cell core temperature and surface temperature was up to 3.4°C during 7C charging while less than 0.2°C during 1C charging. We estimated heat generation of the cell and found that the average heat generation rate during 7C constant current charging was 34 times higher than that during 1C charging. The temperature gradient was smaller but the temperature increase was higher with natural air convection than those with forced convection. A temporary voltage drop phenomenon was observed during 7C charging with forced convection and 5C charging with natural convection, in similar SOC range from ∼22% to ∼40%. The phenomenon can be attributed to drop of cell resistance with rapid temperature rise and slow increase of open circuit voltage in the SOC range.